Protected area effectiveness in a sea of palm oil: A Sumatran case study. (June 2019) - Poor, Erin E.; Frimpong, Emmanuel; Imron, Muhammad Ali; Kelly, Marcella J.
Abstract: Despite the establishment of a national protected area system at the beginning of the 20th century to protect some of the world's most biodiverse forests, Indonesia has one of the highest deforestation rates in the world, due in part to the expansion of the global palm oil industry. The unique ecosystems of Sumatra, Indonesia provide habitat for critically endangered Sumatran tigers ( Panthera tigris sumatrae ), Sumatran elephants ( Elephas maximus sumatrensis ), and two species of orangutans ( Pongo abelii and Pongo tapanuliensis ). In this study, we use a matching method with generalized boosted models to determine the effectiveness of three nationally protected areas in preventing deforestation from 2002 to 2016. We also examine leakage – an increase in deforestation directly outside of protected areas relative to the wider landscape – to provide a clearer picture of the effects of agricultural expansion in this landscape. We found that Tesso Nilo National Park, with its lowland rain forest and conditions suitable for oil palm, offered the least protection from deforestation (avoided deforestation rate = 4.18%, p  < 0.05 95% CI [1.97% - 6.45%]). Bukit Tigapuluh National Park, which may experience some de facto protection (i.e. protection due to factors independent of policy) with its mountainous terrain and difficult access, had the highest avoided deforestation rate (26.36%, p  < 0.05 95% CI [24.17–28.55]), but had relatively high leakage (10.21%, p  < 0.05 95% CI [7.51–12.98]). The low avoided deforestation rate in Tesso Nilo could be due to high localized human population and/or other socio-economic factors we were unable to control for in this study. The quantitative evidence of deforestation and effectiveness of protected areas in this heavily modified landscape supports the need for increased enforcement around protected areas locally, and globally in other oil palm production regions. These actions are critical in the preservation of global, tropical endemic flora and fauna. Indonesian abstract: Meskipun telah membangun sistem kawasan konservasi sejak awal abad ke 20 untuk melindungi hutan dengan keanekaragaman hayati yang sangat tinggi, Indonesia masih merupakan negara yang memiliki laju deforestasi yang tertinggi di dunia, akibat penkembangan industri sawit di dunia. Ekosistem-ekosistem endemic di Sumatera-Indonesia merupakan habitat bagi spesies-spesies yang memiliki status konservasi kritis yaitu harimau Sumatera ( Panthera tigris sumatrae ), gajah Sumatera ( Elephas maximus sumatrensis ), dan dua species orangutan ( Pongo abelii dan Pongo tapanuliensis ). Dalam penelitian ini, kami menggunakan metode matching dengan model generalized boosted untuk menentukan efektivitas dari tiga kawasan konservasi dalam mencegah terjadinya deforestasi dari tahun 2002–2016. Kami juga menilai leakage (kebocoran) – yang merupakan kenaikan laju deforestasi pada area yang berdekatan dengan kawasan konservasi– untuk memberikan gambaran yang utuh atas dampak industri sawit dunia. Kami menemukan bahwa Taman Nasional Tesso Nilo, dengan habitat dan kondisi hutan tropis dataran rendah, yang juga sesuai untuk tanaman sawit, merupakan kawasan konservasi yang memiliki kemampuan paling rendah dalam melindungi dari deforestasi (laju pencegahan deforestasi = 4.18%, p  < 0.05 95% CI [1.97% - 6.45%]). Sedangkan Taman Nasional Bukit Tigapuluh yang merupakan kawasan pegunungan memiliki laju pencegahan deforestasi tertinggi (26.36%, p  < 0.05 95% CI [24.17–28.55]), namun memilki nilai kebocoran yang relatif tinggi (10.21%, p  < 0.05 95% CI [7.51–12.98]). Fakta kuantitatif dari deforestasi dan efektivitas kawasan konservasi pada landskap yang termodifikasi sangat berat ini mengkonfirmasi adanya kebutuhan yang mendesak untuk melakukan penguatan di sekitar kawasan konservasi baik di tingkat lokal maupun global pada wilayah yang ditujukan untuk produksi sawit. Aksi-aksi tersebut sangat dibutuhkan untuk mendukung perlindungan flora dan fauna endemik di dunia.